Perceptions regarding climate change and its health impact: Reflections from a community-based study in India - Vinay Tripathi; Rais Akhtar; G S Preetha (Wolters Kluwer Medknow Publications, 2021)
Background: In the climate change discourse, a body of scholarship focusing on how people perceive climate change and its impact is increasing. However, in the Indian context, such scholarship is limited. Objective: This paper aims to describe the perceptions of people on climate change and its health impacts, which were captured as part of a larger study. Methodology: A cross-sectional study was conducted in randomly selected 983 households in four districts spread across Madhya Pradesh and Jammu and Kashmir. A semi-structured questionnaire was used to collect the data. Results: For 72% of respondents, the perception was not related to climate change per se. Their perceptions were contextual and were based on the anomalies which are observed in the immediate weather conditions. The health impacts of climate change were also not understood at the first place, but with probing 64% of respondents were able to report seasonal diseases. Conclusion: Perceptions of the people regarding climate change are more linked to their own experiences with their local weather conditions rather than the overall concept. This also explains their lack of comprehension about the health impact of climate change, but a sound understanding of seasonal diseases.